Front Cover: Chemical–biological approaches for the direct regulation of cell–cell aggregation. Issue 2 (24th April 2022) - Ma, Jia‐Yi; Wang, Ya‐Xin; Huang, Yan; Zhang, Yi; Cui, Yun‐Xi; Kong, De‐Ming
Abstract : Cell‐cell aggregation is one of the most well‐known modes of intercellular communication. In article number 2022, 2, e166, De‐Ming Kong and co‐workers have reviewed the recent advanced technologies that can artificially regulate cell‐cell aggregation through chemical‐biological approaches. The applications of those cell‐cell aggregation in different fields such as tissue engineering and cell‐based therapy were also proposed.